PROBLEMS OF TEACHING MUSIC TO PRESCHOOL CHILDREN (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the main issues in teaching preschool children to sing, emphasizing the psychological, physiological, pedagogical, and methodological challenges that arise in the early stages of vocal education. Singing is one of the most natural and accessible forms of musical expression, and its development in preschool children plays a crucial role in shaping auditory perception, language acquisition, emotional intelligence, and creativity. However, teaching young children to sing effectively requires sensitivity to their developmental characteristics, including limited vocal range, short attention span, and individual differences in musical ability.